Feeding regimens reshape rumen microbiota and metabolome in Shorthorn cattle: a multi-omic insight into microbial diversity and metabolic pathway dynamics - Dai, SiFan; He, ShiChun; Zhao, ShuSheng; Li, Qing; Mao, HuaMing; Wu, DongWang (Frontiers in Microbiology, 2025)
The rumen microbiome plays a central role in ruminant nutrition and health. To investigate the effects of different feeding regimens on it, this study employed multi-omics analysis to reveal how natural grazing versus intensive feeding alters the rumen microbiota and metabolites in Shorthorn cattle. A total of 18 male shorthorn cattle of about 17 months of age and similar body weight were selected and randomly divided into 3 groups: natural grazing bull group (DJCF), intensive feeding bull group (DJCY) and intensive feeding steer group (DJC). The experiment period was 361 days. After the fattening trial, rumen fluid was collected at slaughter. Microbiota and metabolites were analyzed by 16S rRNA sequencing and LC–MS, and correlations were assessed. The results indicate that different feeding regimens were strongly associated with shifts in rumen microbial diversity and community composition. The ACE and Shannon indices of DJCF group were significantly higher than those of DJCY and DJC group (p < 0.05). Bacteroidetes and Firmicutes were the dominant phyla, with relative abundances of 57.62% (DJCF), 54.11% (DJCY), 48.84% (DJC) and 34.07, 38.31, 43.08%, respectively, showing no significant differences (p > 0.05). At the genus level, Prevotella and Rikenellaceae_RC9_gut_group were dominant. The abundance of Prevotella was highest in DJCY (22.52%), significantly differing from DJC (12.43%; p < 0.05), while Rikenellaceae_RC9_gut_group abundances were 12.56% (DJCF), 9.92% (DJCY), and 11.89% (DJC). In the fungal community, Neocallimastigomycota and Ascomycota were the dominant phyla, and there were no significant differences among the three groups. At the genus level, Caecomyces, the highest in the DJC group, with a significant difference from the DJCF group (p < 0.05). Orpinomyces, the highest in the DJCF group, with significant differences from the DJCY and DJC groups (p < 0.05). There were significant differences in rumen metabolites between different groups, and a variety of different metabolites were identified, involving sucrose and starch metabolism, purine metabolism and other pathways (p < 0.05). In addition, there was a significant correlation between rumen microbes and metabolites (p < 0.05). Thus, an intensive feeding system altered the rumen microbiome, resulting in improvements of Shorthorn cattle growth. Nevertheless, the specific causal relationships and underlying regulatory mechanisms governing the interplay between rumen microbiota and metabolic processes remain to be further elucidated through in-depth investigations.